Effective Cell Growth Potential of Mg-Based Bioceramic Scaffolds towards Targeted Dentin Regeneration - Kontonasaki E.; Bakopoulou A.; Theocharidou A.; Theodorou G. S.; Papadopoulou L.; Kantiranis N.; Bousnaki M.; Chatzichristou C.; Papachristou E.; Paraskevopoulos K.M; Koidis P. (Balkan Stomatological Society, 2015)
New emerging approaches in tissue engineering include incorporation of metal ions involved in various metabolic processes, such as Cu, Zn, Si into bioceramic scaffolds for enhanced cell growth and differentiation of specific cell types. The aim of the present work was to investigate the attachment, morphology, growth and mineralized tissue formation potential of Dental Pulp Stem Cells (DPSCs) seeded into Mg-based glassceramic scaffolds with incorporated Zn and Cu ions. Bioceramic scaffolds containing Si 60%, Ca 30%, Mg 7.5% and either Zn or Cu 2.5%, sintered at different temperatures were synthesized by the foam replica technique and seeded with DPSCs for up to 21 days. Scanning Electron Microscopy with associated Energy Dispersive Spectroscopy (SEM-EDS) was used to evaluate their ability to support the DPSCs's attachment and proliferation, while the structure of the seeded scaffolds was investigated by X-Ray Diffraction Analysis (XRD). Zn-doped bioceramic scaffolds promoted the attachment and growth of human DPSCs, while identically fabricated scaffolds doped with Cu showed a cytotoxic behaviour, irrespective of the sintering temperature. A mineralized tissue with apatite-like structure was formed on both Cu-doped scaffolds and only on those Zn-doped scaffolds heat-treated at lower temperatures. Sol-gel derived Zn-doped scaffolds sintered at 890oC support DPSC growth and apatite-like tissue formation, which renders them as promising candidates towards dental tissue regeneration.